PENCIPTAAN DESTINATION BRANDING KERATON KASUNANAN SOLO SEBAGAI UPAYA MENINGKATKAN MINAT KUNJUNGAN WISATAWAN DOMESTIK - Permana, Aan Ari; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Surakarta is known as a cultural heritage that has very diverse objects of historic legacy in the Middle East with the cultural diversity of the square as the influence of the phenomenon alkuturasi 3 Budaya.Timbulnya shift cultural values embodied in the philosophy that there is The square Hardiningrat. Because it takes a creation of a destination Branding Profile Books square Hardiningrat. To raise the cultural values such as the meaning, culture, philosophy and mythology contained in square Hardiningrat an effort to increase the interest of domestic tourists. Creation is based on the observation, interview and study the existing keyword menggunakansudut view the literature study, the aesthetic, social and cultural self-image and cultural products. By using the analytical method, which is supported by qualitative indicators STP and USP (Unique Selling Proposition) got